Efficacy and safety of conventional synthetic, biologic, and targeted synthetic disease-modifying antirheumatic drugs in rheumatoid arthritis-interstitial lung disease: A narrative review - Richard Conway; Luke Corcoran; Elena Nikiphorou (Indian Journal of Rheumatology)
The range of therapeutic options available for rheumatoid arthritis (RA) is becoming increasingly diverse. Conventional synthetic disease-modifying antirheumatic drugs (DMARDs), biologic DMARDs, and targeted synthetic DMARDs offer the rheumatologist a far greater breadth of treatment options than before. When choosing a treatment in the individual patient, several important factors need to be considered, one of which is the safety in RA interstitial lung disease (RA-ILD). Rheumatologists frequently encounter RA patients with RA-ILD or other co-existing lung diseases. The pulmonary safety profile of our medications is difficult to ascertain and as they are generally infrequent, adverse events are rarely identified in the initial treatment trials. The concern for the safety of these treatments has largely emerged from real-world observational data and has often been based on small numbers of case studies or retrospective analyses of observational studies. The evidence has been controversial with many agents implicated both in the context of predisposing or worsening the risk of ILD and at the same time as potentially beneficial treatments in delaying the onset or progression of ILD. As a result, clear guidance on the treatment of RA-ILD is generally lacking. The purpose of this article, therefore, is to detail our current knowledge of the safety of DMARDs in RA-ILD.